(untitled) (ENTHYMEMA, 2019)
This article offers a new interpretation of The Turn of the Screw. The reader is not asked to choose between ghosts and hallucinations, but rather to understand that James’ intention was to include a ghost story in a story of hallucinations. These two stories intertwine and transform into one another. Nonetheless, the mental dimension remains prevalent: The Turn of the Screw is a tale of identity or rather of the dissolution of the principium individuationis and the consequent establishment of a “confusive regime”. The rise in personal pronouns is the detail that points to and confirms this interpretation.